Fomitopsis betulina (formerly Piptoporus betulinus): the Iceman’s polypore fungus with modern biotechnological potential - Pleszczyńska, Małgorzata (World J Microbiol Biotechnol, 2017)
Higher Basidiomycota have been used in natural medicine throughout the world for centuries. One of such fungi is Fomitopsis betulina (formerly Piptoporus betulinus), which causes brown rot of birch wood. Annual white to brownish fruiting bodies of the species can be found on trees in the northern hemisphere but F. betulina can also be cultured as a mycelium and fruiting body. The fungus has a long tradition of being applied in folk medicine as an antimicrobial, anticancer, and anti-inflammatory agent. Probably due to the curative properties, pieces of its fruiting body were carried by Ötzi the Iceman. Modern research confirms the health-promoting benefits of F. betulina. Pharmacological studies have provided evidence supporting the antibacterial, anti-parasitic, antiviral, anti-inflammatory, anticancer, neuroprotective, and immunomodulating activities of F. betulina preparations. Biologically active compounds such as triterpenoids have been isolated. The mushroom is also a reservoir of valuable enzymes and other substances such as cell wall (1→3)-α-d-glucan which can be used for induction of microbial enzymes degrading cariogenic dental biofilm. In conclusion, F. betulina can be considered as a promising source for the development of new products for healthcare and other biotechnological uses.